DEFORMATION OF SHAFTS AND AXLES LOADED WITH TRANSVERSE FORCE APPLIED IN THEIR CONSOLE PARTS - Sokolovski, Slavcho; Slavtcheva, Evguenia; Deliiski, Nencho (Innovation in Woodworking Industry and Engineering design, 2014)
The methodology for calculation of the shafts and the axles subjected to deformation taking into account the radial clearance in the bearings is presented in the paper.Deflection of the shafts and axles is determined for two cases: the first one is when the antifriction bearings are assumed to be perfectly solid supports and the second one is when the above-mentioned are assumed to be elastic.The deflection of the antifriction bearings is a sum of the initial clearance and the elastic deformations of the antifriction bodies and their rings.The aim of the present work is to determine the elastic deformations of the antifriction bodies and the rings of the bearings.